Pengaruh Senam Lansia Terhadap Tekanan Darah Pada Lanjut Usia Dengan Hipertensi Di Posyandu Lanjut Usia Di Desa Wotgaleh Sukoharjo - Jatiningsih, Kunti; , Agus Sudaryanto, S.Kep., Ns., M.Kes; , Faizah Betty R, A. S. Kep., M. Kes (2016)
Hypertension is the third leading cause of death after stroke and tuberculosis, which reached 6.7% of the population of deaths in all age groups in Indonesia. One of elderly physical deterioration that often occurs is the deterioration of the cardiovascular system. Heart valves become thickened and stiff, reduced heart rate response to stress, loss of elasticity of blood vessels, increased blood pressure due to peripheral vascular resistance. Tight blood pressure control in the elderly associated with the prevention of an increase in blood pressure control. Physical activity such as exercise in the elderly is done regularly will improve physical fitness, thus indirectly exercise can improve heart function and lower blood pressure and reduce the risk of accumulation of fat in the blood vessel walls so that it will maintain its elasticity. The aim of the research know the effect of exercise on blood pressure in elderly with hypertension. This type of research used experimental or quasi-experimental pre. The research design used is one group pretest posttest. The sample was done by using a non probability sampling with pueposive sampling method. The research instrument in the form of elderly exercise 3 times in 1 week. Each therapy exercises performed for 40 minutes. Data analysis technique used was Wilcoxon Signed Ranks. The survey results revealed an average systolic blood pressure before exercise elderly at 167,50 mmHg and after elderly exercise average systolic blood pressure becomes 161.47 mmHg. As for diastolic blood pressure an average of 88,47 mmHg before exercise and after exercise average blood pressure becomes 82,22 mmHg. The Influence elderly exercise on blood pressure of the Elderly with Hypertension in Elderly Health Center in Wotgaleh Sukoharjo.